2018
DOI: 10.1016/j.matchemphys.2017.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and surface structuring of Ge20Sb5S75 amorphous chalcogenide thin films deposited by spin-coating and vacuum thermal evaporation

Abstract: Thin amorphous films of Ge20Sb5S75 composition have been deposited by spin-coating and vacuum thermal evaporation techniques. Their optical properties were investigated by spectroscopic ellipsometry in UV-NIR spectral region. We report on the comparison of thermoand photo-induced changes in optical parameters, structure and chemical resistance of studied samples. Induced changes of films structure connected with changes of chemical stability were exploited for their surface structuring by photolithography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
(91 reference statements)
3
19
0
Order By: Relevance
“…The Raman spectra confirm that annealing of solution processed As30Se70 thin films induces structural polymerization similar to the As-S or Ge-S spin-coated thin films [19,20,26]. The spectra show that the bands of Se8 rings and arsenic rich As4Se4 units are proportionally decreasing while the intensity of AsSe3/2 trigonal pyramids band is increasing.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The Raman spectra confirm that annealing of solution processed As30Se70 thin films induces structural polymerization similar to the As-S or Ge-S spin-coated thin films [19,20,26]. The spectra show that the bands of Se8 rings and arsenic rich As4Se4 units are proportionally decreasing while the intensity of AsSe3/2 trigonal pyramids band is increasing.…”
Section: Resultsmentioning
confidence: 52%
“…Previous research has confirmed, that As-S ChGs can be successfully dissolved in volatile amines with short aliphatic chain (such as n-propylamine or n-butylamine) [15,16,19,20]. In this work, we have also used the n-propylamine (PrNH2) solvent for As30Se70 ChG dissolution.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The system includes a silicate and a crystalline holder. The measurement accuracy is 1 nm that can measure and control the thickness of the layer in during of coating process …”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…26 Enhanced optical properties can also be achieved by thin film deposition through spin coating. 27 Spin-coated films have an increase in interface area and high heat transfer rate for heat removal process in large-scale fabrication. 24,28 The spin-coated graphene films exhibit highly ordered lamellar structure with high orientation of graphene which provides constant thermally conductive pathways.…”
Section: Introductionmentioning
confidence: 99%